PEMANFAATAN SERBUK DAUN SIRIH (Piper betle) UNTUK MENINGKATKAN KESEHATAN IKAN NILA (Oreochromis niloticus) - Zainuddin Zainuddin; Sri Rahmaningsih; Ummul Firmani (Jurnal Perikanan Pantura (JPP), 2018)
This research was conducted to determine the effectiveness of betel leaf powder mixed inthe feed (pellet) to improve the health status of tilapia by measuring the value of erythrocytes andleukocytes. Measurements of erythrocyte values and blood leucocytes of tilapia were performedafter the test fish were fed with betel leaf powder (0.3 g / 100 g feed, 0.6 g / 100 g feed, 0.9 g /100 g feed) for 6week maintenance period. While the control fish during the maintenance periodwas fed pellet feed which was not mixed with betel leaf powder. The erythrocyte and leukocytevalues of tilapia were measured weekly by taking blood in the caudal vein section (tail) of thetest fish. Blood collection was performed using a sterile syringe size of 26 g, which was firstwetted EDTA (Ethylene diamine tetra acetic acid) As an anticoagulant of blood cells asanticoagulants. Furthermore, the blood has been collected in Eppendorf tube which has also beenwetted EDTA (Ethylene diamine tetra acetic acid), then prepared by adding hayem and turksolution and then measured the erythrocyte value and the leukocyte count with Haemometer. Thebest measurements result was at the dose of 0.3 g / 100 g of feed which showed that the amountof erythrocyte of tilapia increased from 1,145,000 cells / mm-3 (week I) to 1,986,667 cells / mm-3(week IV) the number of leukocytes increased from 21,976 cells / mm-3 (week I) to 28,167 cells /mm-3 (week IV). From the results of this study showed that the addition of betel leaf powder inthe feed can improve the health status of tilapia fish.